2011
DOI: 10.1007/s11207-011-9910-7
|View full text |Cite
|
Sign up to set email alerts
|

White-Light Observations and Polarimetric Analysis of the Solar Corona During the Eclipse of 1 August 2008

Abstract: In order to study the solar corona during eclipses, a new telescope was constructed. Three coronal images were obtained simultaneously through a single objective of the telescope as the coronal radiation passed through three polarizers (whose transmission directions were turned 0°, 60°, and 120°in the chosen direction); one image was obtained without a polarizer. The telescope was used to observe the solar corona during the eclipse of 1 August 2008. We obtained the distributions of polarization brightness, K-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…Hanaoka et al [] measured the brightness of the 1 August 2008 solar eclipse and concluded that the solar activity was the lowest in one hundred years, and the coronal brightness was very low. On the same eclipse Figure 5 in Skomorovsky et al [] indicates that at a distance of 1.2 R ⊙ from the Sun center the equator was ∼ 5 times brighter than at the equivalent distance in the pole. Lamy et al [] measured that the solar minimum during the solar cycle 23/24 (2008–2009) was 24% fainter than the minimum during the previous cycle 22/23 (1995–1996) and that the two hemispheres experienced different reductions, 17% for the north and 29% for the south.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Hanaoka et al [] measured the brightness of the 1 August 2008 solar eclipse and concluded that the solar activity was the lowest in one hundred years, and the coronal brightness was very low. On the same eclipse Figure 5 in Skomorovsky et al [] indicates that at a distance of 1.2 R ⊙ from the Sun center the equator was ∼ 5 times brighter than at the equivalent distance in the pole. Lamy et al [] measured that the solar minimum during the solar cycle 23/24 (2008–2009) was 24% fainter than the minimum during the previous cycle 22/23 (1995–1996) and that the two hemispheres experienced different reductions, 17% for the north and 29% for the south.…”
Section: Introductionmentioning
confidence: 84%
“…For example, the task of simultaneous imaging was successfully accomplished by von Klüber [] as far back as the total solar eclipse of 25 February 1952 by splitting the beam to four identical cameras that were cross calibrated. A similar instrumental concept was used by Skomorovsky et al [] to characterize the solar corona in conjunction with the total solar eclipse of 1 August 2008. However, to create synoptic maps of the coronal electron temperature and bulk flow speed over a complete solar rotation, the use of a coronagraph is inevitable and we present the following ideas to create such maps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Imaging-polarimetry during solar eclipses has a history of more than one hundred years. Most researchers detected highly polarized radiations from the corona and presented highly structured polarization maps (for instance, Ney et al, 1961;Eddy and McKim Malville, 1967;Blackwell and Petford, 1966;Hyder, Mauter, and Shutt, 1968;McDougal, 1971;Koutchmy and Schatten, 1971;Molodensky, 1973;Badalyan and Sýkora, 1997;Kulijanishvili and Kapanadze, 2005;Skomorovsky et al, 2012;Qu et al, 2013). More efficient, improved diagnostic methods (House, 1977;House, Querfeld, and Rees, 1982;Raouafi, Lemaire, and Sahal-Bréchot, 1999;Raouafi, Sahal-Bréchot, and Lemaire, 2002;Raouafi and Solanki, 2003;Raouafi, 2005) have been devised to reveal distributions of electron density, electron temperature, and especially the magnetic field, which is highly relevant here and cannot be accurately diagnosed by non-polarimetric measurements.…”
Section: Introductionmentioning
confidence: 99%